Inhibitory suppression of heterogeneously tuned excitation enhances spatial coding in CA1 place cells - Grienberger, Christine; Milstein, Aaron D; Bittner, Katie C; Romani, Sandro; Magee, Jeffrey C (Nature neuroscience, 2017)
The authors investigate the role of inhibition in shaping spatial selectivity of CA1 place cells. Combining whole-cell recordings, optogenetics and computational modeling, they demonstrate that inhibition enhances both rate and temporal coding of space by counteracting noise from broad out-of-field excitation. Place cells in the CA1 region of the hippocampus express location-specific firing despite receiving a steady barrage of heterogeneously tuned excitatory inputs that should compromise output dynamic range and timing. We examined the role of synaptic inhibition in countering the deleterious effects of off-target excitation. Intracellular recordings in behaving mice demonstrate that bimodal excitation drives place cells, while unimodal excitation drives weaker or no spatial tuning in interneurons. Optogenetic hyperpolarization of interneurons had spatially uniform effects on place cell membrane potential dynamics, substantially reducing spatial selectivity. These data and a computational model suggest that spatially uniform inhibitory conductance enhances rate coding in place cells by suppressing out-of-field excitation and by limiting dendritic amplification. Similarly, we observed that inhibitory suppression of phasic noise generated by out-of-field excitation enhances temporal coding by expanding the range of theta phase precession. Thus, spatially uniform inhibition allows proficient and flexible coding in hippocampal CA1 by suppressing heterogeneously tuned excitation.